Pengaruh Kepuasan Kerja Dan Komitmen Organisasi Terhadap Turnover Intentions Karyawan (Survey Pada PT. Telesindo Shop Cabang Pekanbaru) - Rahmat, Adi (Jurnal Daya Saing, 2015)
Abstract: This research was conducted at PT. Telesindo Shop Branch Pekanbaru. The purpose of the study to determine the effect of job satisfaction and organizational commitment on employee turnover intentions PT. Telesindo shop pekanbaru branch. To achieve these objectives the research conducted by using the sample of 41 people, using census method. Methods of data analysis using descriptive and quantitative. Based on the test results bedasarkan job satisfaction variables (X1) using SPSS acquired thitung -3.082. So = 5%, which is equal to 2.028awhen compared to the significant ttabel can be seen that large thitung lebih of ttable (-3.082> 2.028), thus it can be concluded that the variables X1 or negatively affects job satisfaction and turnover intentions significant to the employees of PT. Telesindo shop Pekanbaru branch. Based on the results of tests on X2 (organizational commitment) obtained thitung sebesar -4,131dengan comparison with ttabel 2.028 (attachment), it can be seen that t count> ttable (-4.131> 2.028). Thus it can be concluded that the variable X¬2 (organizational commitment) partially have a strong relationship in influencing turnove rintentions employees of PT. Telesindo shop Pekanbaru branch. Thus we can conclude that organizational commitment variable partially has a strong influence in affecting turnove rintentions employees of PT. Telesindo shop Pekanbaru branch. Recommendations can be submitted is at. Telesindo shop Pekanbaru branch, in order to further enhance the variable job satisfaction and work environment in which respondents on indicators of employee relations affect the performance of the employees received a low response of respondents with low responder on these indicators will affect employees in improving their performance. Keywords: Job Satisfaction, Organizational Commitment and Performance turnover intention